Nutritional quality of complementary food prepared from unmalted and malted maize fortified with cowpea using extrusion cooking - Obatolu, V.; Cole, A.; Maziya-Dixon, B.B. (Wiley, 2000)
The nutritional quality of extruded unmalted or malted maize fortified with cowpea as complementary food was assessed based on its proximate analysis, amino acid composition and results from rat feeding with the blends. Results indicated a slight decrease and increase in protein content due to malting and extrusion respectively. The changes in fat, crude fibre and ash content were not significant. The blends were a good source of energy, ranging from 1831 to 2045 kJ per 100 g. Extrusion significantly increased the amino acid content of the blends, while malting had a varied effect on each of the amino acids. There was no significant difference in the protein efficiency ratio (PER), net protein ratio (NPR) and weight gain of rats fed the blends when compared with the control (casein diet). The present study shows that malting improved the nutritional quality of the blends. Rats fed the casein diet had higher values for total digestibility (TD) and net protein utilisation (NPU). There was no significant difference (P > 0.05) in the internal organ weights of rats fed all blends except the protein-free diet.